Accuracy of a wearable sensor for measures of head kinematics and calculation of brain tissue strain - Knowles, B. M.; Yu, H.; Dennison, C. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Wearable kinematic sensors can be used to study head injury biomechanics based on kinematics and, more recently, based on tissue strain metrics using kinematics-driven brain models. These sensors require in-situ calibration and there is currently no data conveying wearable ability to estimate tissue strain. We simulated head impact (n = 871) to a 50th percentile Hybrid III (H-III) head wearing a hockey helmet instrumented with wearable GForceTracker (GFT) sensors measuring linear acceleration and angular velocity. A GFT was also fixed within the H-III head to establish a lower boundary on systematic errors. We quantified GFT errors relative to H-III measures based on peak kinematics and cumulative strain damage measure (CSDM). The smallest mean errors were 12% (peak resultant linear acceleration) and 15% (peak resultant angular velocity) for the GFT within the H-III. Errors for GFTs on the helmet were on average 54% (peak resultant linear acceleration) and 21% (peak resultant angular velocity). On average, the GFT inside the helmet overestimated CSDM by 0.15.